Inhibitory action of gonadotropin‐inhibitory hormone on the signaling pathways induced by kisspeptin and vasoactive intestinal polypeptide in GnRH neuronal cell line, GT1–7. Issue 6 (29th February 2016) - Son, You Lee; Ubuka, Takayoshi; Soga, Tomoko; Yamamoto, Kazutoshi; Bentley, George E.; Tsutsui, Kazuyoshi
ABSTRACT: Gonadotropin‐inhibitory hormone (GnIH) acts as a negative regulator of reproduction by acting on gonadotropes and gonadotropin‐releasing hormone (GnRH) neurons. Despite its functional significance, the molecular mechanism of GnIH action in the target cells has not been fully elucidated. To expand our previous study on GnIH actions in gonadotropes, we investigated the potential signal transduction pathway that conveys the inhibitory action of GnIH in GnRH neurons by using the GnRH neuronal cell line, GT1–7. We examined whether GnIH inhibits the action of kisspeptin and vasoactive intestinal polypeptide (VIP), positive regulators of GnRH neurons. Although GnIH significantly suppressed the stimulatory effect of kisspeptin on GnRH release in hypothalamic culture, GnIH had no inhibitory effect on kisspeptin stimulation of serum response element and nuclear factor of activated T‐cell response element activities and ERK phosphorylation, indicating that GnIH may not directly inhibit kisspeptin signaling in GnRH neurons. On the contrary, GnIH effectively eliminated the stimulatory effect of VIP on p38 and ERK phosphorylation, c‐Fos mRNA expression, and GnRH release. The use of pharmacological modulators strongly demonstrated the specific inhibitory action of GnIH on the adenylate cyclase/cAMP/protein kinase A pathway, suggesting a common inhibitory mechanism of GnIH action in GnRH neurons and gonadotropes.—Son, Y. L., Ubuka, T., Soga, T., Yamamoto, K., Bentley, G. E., Tsutsui, K. Inhibitory action of gonadotropin‐inhibitory hormone on the signaling pathways induced by kisspeptin and vasoactive intestinal polypeptide in GnRH neuronal cell line, GT1–7. FASEB J. 30, 2198–2210 (2016). www.fasebj.org